The origins and end-organ consequence of pre-eclampsia. - Eastabrook, G; Brown, M; Sargent, I (2011)
Pre-eclampsia is a multisystem disorder with profound implications for both mother and fetus. Its origins lie in the earliest stages of pregnancy. Abnormal interactions between fetal trophoblast and maternal decidua, including the cells of the maternal immune system, lead to inadequate placental invasion and maternal vascular remodelling. However, abnormal placentation is only one step in the cascade of events that ultimately result in maternal organ dysfunction. Pre-existing maternal conditions predisposing to inflammation and vascular pathology, fetal factors, including multiple gestations and macrosomia, and environmental exposures, including infection, may contribute to the release of placental substances, including anti-angiogenic molecules, into the maternal circulation. These may act directly or indirectly upon the endothelia of end organs, including the kidney, liver and brain. The liberation of reactive oxygen species, cytokines, and microthrombi from damaged endothelia contribute further to organ damage. In studying the normal processes that occur during human placentation and early pregnancy, we will develop a greater understanding of what may go awry in pre-eclampsia. Such research will be crucial in discovering novel biomarkers for prediction of the disorder and, eventually, in finding targets for effective interventions.